2013
DOI: 10.6061/clinics/2013(02)oa09
|View full text |Cite
|
Sign up to set email alerts
|

Enteral nutrition discontinuation and outcomes in general critically ill patients

Abstract: OBJECTIVE:To determine the relationship between enteral nutrition discontinuation and outcome in general critically ill patients.MATERIALS AND METHODS:All patients admitted to a mixed intensive care unit in a tertiary care hospital from May-August 2009 were screened for an indication for enteral nutrition. Patients were followed up until leaving the intensive care unit or a maximum of 28 days. The gastrointestinal failure score was calculated daily by adding values of 0 if the enteral nutrition received was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
15
0
4
Order By: Relevance
“…The other 2 studies could not be evaluated for quality since 1 was a study reported as an abstract awaiting full text publication, whereas the other was a commentary letter . Using the GRADE criteria, 4/12 studies scored “high” (score 4–5), 3/12 scored “low” (score 2), and 5/12 scored “very low” (score ≤1) . Using the NIH scale, 8/12 studies were of “fair” quality, 3/12 were “good,” and 1/12 study was “poor.” Based on ROBINS‐I quality classification, 10/12 studies scored “moderate risk of bias,” 1/12 scored “serious risk of bias,” 1/12 scored “low risk of bias,” and 1 study tool was developed from a randomized controlled clinical trial which scored “fair” using the Cochrane classification for randomized controlled trials …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The other 2 studies could not be evaluated for quality since 1 was a study reported as an abstract awaiting full text publication, whereas the other was a commentary letter . Using the GRADE criteria, 4/12 studies scored “high” (score 4–5), 3/12 scored “low” (score 2), and 5/12 scored “very low” (score ≤1) . Using the NIH scale, 8/12 studies were of “fair” quality, 3/12 were “good,” and 1/12 study was “poor.” Based on ROBINS‐I quality classification, 10/12 studies scored “moderate risk of bias,” 1/12 scored “serious risk of bias,” 1/12 scored “low risk of bias,” and 1 study tool was developed from a randomized controlled clinical trial which scored “fair” using the Cochrane classification for randomized controlled trials …”
Section: Resultsmentioning
confidence: 99%
“…(1) Study type: 7 of 14 studies 35,[37][38][39]42,44,45 were prospective cohort studies including a risk stratification model 45 and a multimodal strategy management model 44 ; 1 was a retrospective cohort study 40 ; 2 were endorsed recommendations from AGI grading constructed based on a comprehensive quality-graded literature review and expert Figure 1. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow chart illustrating the search strategy and study selection process.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations